(untitled) (Law, State and Telecommunications Review, 2024)
[Purpose] The purpose of this research is to examine the legislative approaches to regulating cryptocurrencies in different states and regions. The aim is to analyze the legal framework of cryptocurrencies in the Kazakh and international economy and determine the modern scientific approaches used in their functioning. [Methodology/Approach/Design] The study employs a combination of theoretical and empirical methods, including analysis, synthesis, historical analysis, comparative analysis, formal-logical methods, and hermeneutics. A comparative analysis is conducted to assess the different regulatory approaches of states towards cryptocurrencies and evaluate the justification for terms such as "digital currency" and "digital asset." [Findings] The findings of this study underscore the necessity for further amendments to the legislation in Kazakhstan, specifically addressing overlooked details and features concerning the financial and legal aspects of cryptocurrencies. Key decisions need to be made regarding their acceptance for public payments, tax considerations, declaration requirements, and recognition as private money. The study emphasizes the significance of adopting a comprehensive and forward-thinking legal approach that supports the full legalization of cryptocurrencies while establishing a robust regulatory framework. This approach would effectively safeguard the interests of individuals and entities, address concerns, and promote a balanced and secure environment.